Need for Survival in “Genomic Market Economy”: Attracting Foreign Investments and Saving Country’s Economy By Adapting Molecular Pathology Diagnosti in Pakistan - Khan , Sikandar Hayat; Khan, Muhammad Qaiser Alam (Pakistan Armed Forces Medical Journal, 2025)
The complexity and cost of baseline laboratory analytics will soon to be challenged by next-generational and innovative biotechnological developments in the field of pathological sciences. The once idealized “Lab on chip & MRI on hand” is just shaping away reality thus superseding human resource, conventional laboratory biotechnology, business yield with projected undesirable as the demise of traditional laboratory.1 Though the rise and fall of medical specialties can be easily predicted to combat the deep-down intricacies of human